2007
DOI: 10.1182/blood-2006-08-039628
|View full text |Cite
|
Sign up to set email alerts
|

Forced expression of Nanog in hematopoietic stem cells results in a γδT-cell disorder

Abstract: Nanog is a key molecule involved in the maintenance of the self-renewal of undifferentiated embryonic stem (ES) cells. In this work we investigate whether Nanog can enhance self-renewal in hematopoietic stem cells. Contrary to our expectation, no positive effect of Nanog transduction was detected in bone marrow reconstitution assays. However, recipients of Nanog-transduced (Nanog) hematopoietic stem cells (HSCs) invariantly develop a unique disorder typified by an atrophic thymus occupied by Nanogexpressing ␥␦… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…4a, Supplementary Table 1). In addition, the thymus was atrophic, which is consistent with the reported effect of Nanog overexpression in the hematopoietic system 30 . Alterations were also observed in the intestine (inflammation and Paneth cell mislocalization).…”
supporting
confidence: 80%
“…4a, Supplementary Table 1). In addition, the thymus was atrophic, which is consistent with the reported effect of Nanog overexpression in the hematopoietic system 30 . Alterations were also observed in the intestine (inflammation and Paneth cell mislocalization).…”
supporting
confidence: 80%
“…The breakthrough of Takahashi and Yamanaka (Takahashi and Yamanaka, 2006) showed that only 4 transcription factors ("four hits") were necessary for induction of pluripotency. Of note, the 4 transcription factors have been shown to play an oncogenic role in different contexts, and both c-Myc and Klf4 are well-known oncogenes Okita et al, 2007;Rowland et al, 2005;Tanaka et al, 2007). This is a clear evidence of the essential mechanistic link between reprogramming and cancer, and illustrates the fact that there are a certain number of genes/proteins that are strong enough so as to induce the change of expression patterns in a global manner affecting cellular identity.…”
Section: Cancer: the Dark Side Of Plasticitymentioning
confidence: 97%
“…Moreover, the expression of Sox2 can be detected in human gastric carcinoma (29), stomach adenocarcinomas (30), pancreatic carcinoma (31), vater adenocarcinoma (32), malignant glioma (33), breast cancer (34), and brain tumors (35). Nanog has also been demonstrated that the forced expression in hematopoietic stem cells can give rise to T cell disorder (36). Klf4 is overexpressed in squamous cell carcinoma (37,38), and Klf4 seems to be involved in other cancer formation process.…”
Section: Tumorgenesis and Risk Of Integrationmentioning
confidence: 99%